ANALISIS KONTRIBUSI PENDAPATAN TENAGA KERJA WANITA PADA USAHA EMPING MELINJO TERHADAP PENDAPATAN KELUARGA DI DESA NOGOSARI PACITAN - Yulti Afrila Ajung; Ramon Syahrial; Dwiyana Anela Kurniasari; Siti Alimah (Jurnal Gesi, 2022)
The purpose of this study was to determine the effect of length of work, age, education level, and number of dependents on the contribution of female workers in family income. This study reveals that female workers in the emping home industry have a role in increasing family income. This study shows that the wages of female workers contribute 8.4% to family income while the remaining 91.6% is influenced by other factors, this indicates that the contribution given is still relatively low because <50%. female workers still live in poor conditions because their income is too small. The economic life of emping melinjo female workers has not changed in their lives because the income earned has not been able to meet secondary and tertiary needs. Suggestions in this study include (1) for the emping home industry in Nogosari Village, it is expected to be able to maintain and be able to add policies that favor workers, and (2) for female workers it is recommended to have skills or side jobs with the aim of increasing the income earned, so that it can provide additional family income